2022
DOI: 10.1002/agt2.291
|View full text |Cite
|
Sign up to set email alerts
|

Substituent‐controlled aggregate luminescence: Computational unraveling of S1/S0 surface crossing

Abstract: We computationally investigated the molecular aggregation effects on the excited state deactivation processes by considering both the direct vibrational relaxation and the S0/S1 surface crossing, that is, the minimum energy conical intersection (MECI). Taking classical AIEgens bis(piperidyl)anthracenes (BPAs) isomers and the substituted silole derivatives as examples, we show that the deformation of MECI always occurs at the atom with greater hole/electron overlap. Besides, the energetic and structural changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The optimized MECI geometry of BFBB-1 was obtained by using a spin-flip time-dependent density functional theory (SF-TDDFT) method (Table S5, ESI †). 27,29 The energies of the key points involved in both vibrational relaxation and S 0 /S 1 surface crossing channels were calculated using the Gaussian 16 package. As shown in Fig.…”
Section: Nonradiative Deactivation Mechanism Of Bfbb-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized MECI geometry of BFBB-1 was obtained by using a spin-flip time-dependent density functional theory (SF-TDDFT) method (Table S5, ESI †). 27,29 The energies of the key points involved in both vibrational relaxation and S 0 /S 1 surface crossing channels were calculated using the Gaussian 16 package. As shown in Fig.…”
Section: Nonradiative Deactivation Mechanism Of Bfbb-1mentioning
confidence: 99%
“…In the past few years, theoretical investigations based on a twochannel model, 24,25 which takes account of both the vibronic relaxation and S 0 /S 1 surface crossing pathways, have revealed that minimum energy conical intersection (MECI) induced by the structural deformation in different types of polyheteroaromatic dyes, 26,27 including BF 2 -containing polyheterocycles, 17,28,29 is actually the underlying channel for their nonradiative decay. Inspired by these reports, we herein specifically synthesized four BF 2 complexes of N-benzoyl 2-aminobenzothiazoles (BFBB-1-4) with or without EDGs as model compounds to address the issues mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…This photophysical behavior has been termed aggregation-induced emission (AIE). After more than 20 years of development in the field of AIE, the working mechanism of restriction of intramolecular motion (RIM) has been established and well-recognized. , RIM can lead to conformational rigidification, thereby suppressing nonradiative decay pathways, e.g., vibronic coupling, conical intersection, and photochemical reactions, thus contributing to the enhanced luminescence process. The discovery and exploration of AIE has also greatly advanced the field of precision medicine and light-based healthcare. , For fluorescence imaging, AIE luminogens (AIEgens) and their formed NPs are endowed with the inherent advantages of low background noise, fair photostability, large Stokes shift, biocompatibility, high brightness, , and deeper tissue penetration and higher spatial resolution. , In particular, the tetraphenylethylene (TPE) skeleton is the most versatile AIEgene because it can be designed to have various desired functions by introducing functional groups or π-extensions …”
Section: Introductionmentioning
confidence: 99%
“… 41 , 43 46 They showed by a theoretical study that this molecule adopts a Dewar-benzene-like nonflat structure at the MECI due to a large structural change from the planar geometry at the Frank–Condon state, together with experimentally confirmed viscosity responsiveness of this molecule. 41 , 47 We expected that its smaller molecular size makes it possible to design highly biocompatible molecules.…”
mentioning
confidence: 99%
“…In this study, we focused on viscosity-responsive fluorescence caused by restricted access to minimum energy conical intersection (MECI). If a large conformational change is required to access the MECI in the excited state, fluorescence of the molecules should be responsive to viscosity since high viscosity of the surrounding environment restricts the transition to the MECI. To demonstrate the application of this strategy for developing viscosity-responsive fluorescent probes that can work in cellular systems, we chose 9,10-bis­( N , N -dialkylamino)­anthracene, reported by Konishi and co-workers. , They showed by a theoretical study that this molecule adopts a Dewar-benzene-like nonflat structure at the MECI due to a large structural change from the planar geometry at the Frank–Condon state, together with experimentally confirmed viscosity responsiveness of this molecule. , We expected that its smaller molecular size makes it possible to design highly biocompatible molecules.…”
mentioning
confidence: 99%